Minimally invasive repair of iatrogenic right ventricular perforation guided by bedside contrast-enhanced ultrasound: A case report and literature review - Zhao, Yanchun; Lin, Yucheng; Hong, Zhiliang; Lai, Baochun; Lian, Lianghua; Chen, Lin; Xie, Qi; Zhou, Xiaofen; Wu, Songsong (Frontiers in Cardiovascular Medicine, 2022)
This case report involves a 93-year-old female patient with atrioventricular block and suffered right ventricular free wall perforation during installation of Micra Leadless Pacemaker (MLP). Pericardial tamponade occurred shortly, and we adopted pericardial catheter drainage as the primary emergency treatment. Considering the patient's physical conditions and leveraging the special treatment facilitates of the Intensive Care Unit (ICU), we tried a new emergency treatment approach. After putting the patient under intravenous anesthesia (no cardiac arrest), we made a small intercostal incision and performed bedside minimally invasive repair of right ventricular free wall perforation. It should be noted that ultrasound played a key role in pinpointing the breach and intraoperative guidance. We first used contrast-enhanced ultrasound (CEUS) to locate the breach. Then guided by bedside ultrasound, we accessed the perforation with the minimum incision size (5 cm). Our experience in this case may serve as a good reference in the emergency treatment for right ventricular free wall perforation.